ВЕРТЕБРОГЕННАЯ ЦЕРВИКАЛЬНАЯ РАДИКУЛОПАТИЯ: КЛИНИЧЕСКИЕ АСПЕКТЫ ДИАГНОСТИКИ И ЛЕЧЕНИЯ - А. А. Фирсов; А. Ю. Кусайкин; А. А. Никонов (Архивъ внутренней медицины, 2012)
Vertebrogenic diseases of the cervical spine are an urgent problem for many decades. The article discusses the clinical aspects of diagnostics and treatment of cervical radiculopathy, in particular the application of the conservative treatment of the pain syndrome, along with non-steroidal anti-inflammatory drugs of Milgamma neurotropic complex.